Credit Management and Performance of selected financial Institutions in Kabale District, Uganda - Joshua, Muhumuza (Kabale University, 2020)
The study investigated the impact of credit management quality on the performance of selected financial institutions in Kabale District. The specific objectives were; to investigate the relationship between key performance indicators (return on equity and return on assets) and non-performing loans; to explore the relationship between capital adequacy ratio and performance (return on equity and return on assets) and to examine the effect of credit terms on loan performance of financial institutions studied. It adopted a case study design. Primary data was collected using questionnaires and interviews. Both qualitative and quantitative data were collected; descriptive statistics were used to analyze the data. The study confirmed that financial institution’s profitability levels decline as a result of increasing non-performing loans as the bank will fail to meet their set targets, bank expense will increase because of collection efforts and shareholder’s return decreases drastically. It also established that to a large extent capital adequacy impacted on the performance of financial institutions studied as capital enhances earnings by reducing expected financial distress; capital makes the institution to remain liquid in the face of non-performing loans and also the bank uses this capital to provide for delinquent loans, which indicates a strong positive relationship between capital adequacy and performance. The study further revealed that to a very great extent credit terms affected loan performance; full collateralization in case the borrower fails to pay, penalty for late payment, flexible repayment periods, loan restructuring and use of credit committees to review big loans increases loan recovery and improves customer’s commitment to repay. The study recommends that there is need for financial institutions to enhance their client appraisal techniques so as to better know customer affordability and improve bank financial performance. Through client appraisal techniques, Character, Capacity, Collateral, Capital and Condition of the client will be better matched to loan size and terms .The financial institutions will be able to know credit worth of clients and thus reduce their non-performing loans and improve loan and overall bank performance. Lastly financial institutions should adhere to the requirements of the Central Bank as failure to do so may lead to their closure; they should also always recapitalize so as to match deposits. Capital is supposed to grow as deposits grow.